2014
DOI: 10.1016/j.bpj.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of the Effect of the S23D/S24D Troponin I Mutation on Cardiac Troponin Structural Dynamics

Abstract: During β-adrenergic stimulation, cardiac troponin I (cTnI) is phosphorylated by protein kinase A (PKA) at sites S23/S24, located at the N-terminus of cTnI. This phosphorylation has been shown to decrease KCa and pCa50, and weaken the cTnC-cTnI (C-I) interaction. We recently reported that phosphorylation results in an increase in the rate of early, slow phase of relaxation (kREL,slow) and a decrease in its duration (tREL,slow), which speeds up the overall relaxation. However, as the N-terminus of cTnI (residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
79
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 48 publications
12
79
3
Order By: Relevance
“…The water forms a hydrogen bond with the coordinating oxygen side chain, allowing the oxygen of the water to become the new coordination atom. In previous computational work (23,24), similar effects were found, and there is a small change in coordinating distance; however, overall, none of these effects can be the cause of the variation in measured dissociation rates. Inspection of the trajectories showed that the N-lobe of the cTnC did have some overall movement, whereas the structure of the Ca 2+ binding pocket remained stable.…”
Section: +supporting
confidence: 71%
See 2 more Smart Citations
“…The water forms a hydrogen bond with the coordinating oxygen side chain, allowing the oxygen of the water to become the new coordination atom. In previous computational work (23,24), similar effects were found, and there is a small change in coordinating distance; however, overall, none of these effects can be the cause of the variation in measured dissociation rates. Inspection of the trajectories showed that the N-lobe of the cTnC did have some overall movement, whereas the structure of the Ca 2+ binding pocket remained stable.…”
Section: +supporting
confidence: 71%
“…S1, the coordinating oxygento-Ca 2+ distances did not change significantly upon mutation; therefore, it is reasonable to assume that the effect on the rate of Ca 2+ release is not due to the coordinating oxygens of the cTnC binding pocket and the strength to which they bind Ca 2+ . This result is complementary to similar work comparing the WT with the cTnI S23D/S24D double mutation (23) and the WT with the cTnI R145G mutation (24). However, with the full CTF model, we are able to investigate the effects of mutations that are not within the core region of cTn.…”
Section: +supporting
confidence: 54%
See 1 more Smart Citation
“…In general, upon introduction of either R145W or T143E, we observed increased mobility of cTnC within the low affinity Site II Ca 2ϩ binding domain. Of note, previous MD simulations have reported altered intramolecular interactions within cTnI between the N terminus and the IP domain upon introduction of the PKA S23D/S24D phosphomimetic, and this was disrupted by the presence of the HCM-associated cTnI R145G mutation (26,40,41). However, we did not see such intramolecular interactions in preliminary MD simulation runs.…”
Section: Discussioncontrasting
confidence: 58%
“…This rearrangement could involve new intramolecular interactions between the NЈ and the inhibitory peptide (IP) domain of cTnI (34). This in turn may strengthen the interaction between cardiac troponin C and the switch peptide domain of cTnI, thereby inducing a reduction in myofilament Ca 2ϩ sensitivity and at the same time weaken the interaction between the IP domain and actin.…”
Section: Discussionmentioning
confidence: 99%